Analysis of Production Efficiency: Comparison of Power Conversion Using Diode and Thyristor in Circular Saw - Budi Kristiyono; Dwi Sari Ida Aflaha (Jurnal Inovasi Pendidikan dan Sains, 2025)
This research aims to evaluate the comparison of two power conversion methods, utilizing diodes and thyristors, in circular saw machines used in the furniture industry. The research used a quantitative approach through controlled experiments, testing five machines from each method based on power consumption, cutting speed, and cutting productivity. The test results showed that machines with thyristor-based power conversion showed higher cutting speed and productivity compared to diode-based machines, although their power consumption was slightly higher. Statistical analysis using Welch’s t-test indicated no significant difference in energy efficiency between the two methods. This study recommends the use of thyristor power conversion for industrial applications that require high speed and productivity, while the diode method is more suitable for low-power requirements